Phone in Hand, Mind Elsewhere: Phubbing, Academic Engagement and Social Connectedness among Nigerian Undergraduates - Lawan Bappah; Umaru Hyelhara Mshelia; Musa Hauwa Babaji (Muslim Education Review, 2026)
Smartphones now occupy a central place in the social lives of university students, yet their consequences for academic engagement and interpersonal connection are not always straightforward. This study examined the prevalence of phubbing, defined as the use of a smartphone during face-to-face interaction, and its associations with academic engagement and social connectedness among 381 undergraduates at the Federal University of Kashere, Nigeria. A correlational survey design was employed, with participants selected through stratified random sampling. Data were collected using validated measures of phubbing, academic engagement and social connectedness. Descriptive statistics and simple linear regression were employed for data analysis. The findings revealed that phubbing was moderately prevalent among undergraduate students. Furthermore, phubbing significantly predicted lower levels of academic engagement and social connectedness, indicating that increased engagement in phubbing behavior is associated with reduced involvement in academic activities and weaker interpersonal connections within the university environment. These findings extend the growing body of evidence on the adverse consequences of phubbing in a Nigerian higher education context and carry implications for digital literacy policy and student support services.